Tính chất cơ học của vật liệu compozit sử dụng prepreg trên cơ sở nhựa phenolic và epoxy gia cường sợi thủy tinh và thủy tinh-aramit - Tùng, Nguyễn Huy; Diệu, Trần Vĩnh; Trung, Đặng Hữu; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2015)
Prepreg composite materials are becoming increasingly common in the industry due to their ease of use, consistent properties and high surface quality. However, there is much to understand about prepreg prior to committing to using this material. Therefore, in this paper phenolic resin (rezolic) and two compositions, including solid epoxy resin DER633U/Hardener DEH84 and epoxy Epikote 828/Hardener Novolac have been investigated for preparing glass fiber and glass-aramid fibers reinforced prepregs. Results showed that all single resin and compositions mentioned above are satisfied technical requirements for prepregs. The best prepreg was made by composition DER633U/DEH84 because it possesses good shelf life at temperature 36-37 oC and high composite mechanical properties. For example, tensile strength 205.2 MPa and Izod impact strength 228.9 KJ/m2 with C-glass fabric reinforcement 360 g/m2.